Impact of the wheelchair in the development of upper body specific muscle training among students Ectomorph - Mohammed Zerf; Beboucha Wahib; Bengoua Ali (Turkish Journal of Kinesiology, 2017)
Ectomorph's body is fragile, with long, slender, poorly muscled extremities and delicate bones. Through this problem, PE teacher must alter its expectations drew upon the changes in body shapes in the early stage of growth. Indeed, in similar as disabling defects due to the lack of general muscular strength via ectomorph body shape. For this proposal, we emphasized the experimental method, including 40 males' ectomorph students, chosen by the intentional method.  Divided into two groups (Experiment (ES), control (CS)) based on upper body muscular disabilities, during the 2016/2017 school year, at Zagllole secondary school, Mostaganem academic. To test our hypothesis, we focused on two training programs traditional with weight (CS) vs Wheelchair (ES) as tools to strengthen upper body musculature, within 6-weeks under researchers' supervision, integrate as 15 minutes of warm-up during basketball cycle in the second semester. Whereas to evaluate their progress, we based on press up test and multiple-RM assessments (Pectoral (Pecs) - Deltoids (Delts) - Latissimus Dorsi (lats) - Biceps- Triceps- Abdominals (Abs)). In the beginning and at the end of the program basketball cycle. Based on statistical applied, we confirmed that the integration of the wheelchair as a strength tool improves the general muscular strength via ectomorph body shape better than the traditional. The wheelchair is a benefited tool muscle training that improves the muscle building, muscle strength and muscle endurance via ectomorph body shape better than the traditional method. Interpret in similar studies via manual wheelchair frames and components as manufactured materials having high strength-to-weight ratios. Finally, we approved in the case of this study that few wheelchair rounds around the gym is enough to improve strength in any strength program.